2003
DOI: 10.1902/jop.2003.74.10.1483
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐Implant Interface Around Titanium Implants Under Different Loading Conditions: A Histomorphometrical Analysis in the Macaca fascicularis Monkey

Abstract: Implant loading might have stimulated increased bone formation and thus may be a key factor in influencing positive osseointegration. In addition, immediately loaded implants may osseointegrate in a similar manner as delayed loaded implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 22 publications
5
93
1
4
Order By: Relevance
“…14,15 Similarly, previous studies using digital subtraction radiography (DSR) found a continuous increase in peri-implant bone density over time following implantation. 16,17 However, these studies do not report reliable quantitative measurements and comparison between different loading protocols is not provided.…”
Section: Introductionmentioning
confidence: 75%
“…14,15 Similarly, previous studies using digital subtraction radiography (DSR) found a continuous increase in peri-implant bone density over time following implantation. 16,17 However, these studies do not report reliable quantitative measurements and comparison between different loading protocols is not provided.…”
Section: Introductionmentioning
confidence: 75%
“…Studies have demonstrated a relationship between implant design and osseointegration. [17][18][19] Rough implant surfaces present a larger surface area and allow a firmer mechanical link to the surrounding tissues. 20 In this study, the used implants share good design and rough surface, and this also may attribute to the high rate of the success.…”
Section: Discussionmentioning
confidence: 99%
“…A las seis semanas, también fue evidente la presencia de vasos sanguíneos en conjunto con una mayor área de remodelación ósea, en acuerdo con los resultados de Chappard et al (1999). La cantidad de tejido conectivo no mineralizado disminuyó en este periodo, pasando el tejido óseo a dominar gran parte de las áreas adyacente y distantes del implante, lo que está en relación a lo establecido por Romanos et al (2003). Aparentemente, la calidad ósea generada por la remodelación del mismo fue similar al hueso preexistente y las características óseas de la región periimplantar y del hueso en contacto con la rosca del implante no mostraron diferencias estructurales, como los señalado por Nkenke et al (2003) en un estudio realizado en cerdos.…”
Section: Discussionunclassified